2022
DOI: 10.1177/19386400221116467
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity After Flatfoot Reconstruction With Lateral Column Lengthening

Abstract: Background The objective of this study was to evaluate return to activity following flatfoot reconstruction with lateral column lengthening (LCL) by assessing functional postoperative data and identifying patient characteristics associated with poor function following surgery. Methods Consecutive patients that underwent operative flatfoot correction including LCL and other necessary procedures from 2014 to 2019 by 3 fellowship trained foot and ankle orthopedic surgeons were retrospectively administered Foot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Prior studies using FAAM scores to assess outcomes of flatfoot deformity correction have shown promising results with a variety of techniques. 2 , 8 , 14 , 17 , 19 In general, preoperatively our patients had poorer scores. Our preoperative FAAM ADL and sports score were 53.9 and 29.7, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…Prior studies using FAAM scores to assess outcomes of flatfoot deformity correction have shown promising results with a variety of techniques. 2 , 8 , 14 , 17 , 19 In general, preoperatively our patients had poorer scores. Our preoperative FAAM ADL and sports score were 53.9 and 29.7, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…Four of seven studies reported no fixation for LCL titanium wedge stabilization [15][16][17][18]. Two studies utilized one or two 2.4 mm cortical screws for titanium wedge stabilization in all patients [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Another study discussed the placement of a lateral plate in conjunction with the LCL titanium wedge but did not discuss the number of patients or indications for this additional fixation [8]. The size of the graft(s) utilized was reported in 6 of 7 of the included studies [8,[15][16][17][18][19] though two studies [15,16] reported a range of the graft size used, not individualized for each patient. Stamatos, et al did not report the graft size used [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations